Mathematical Modeling and Intelligent Optimization in Green Manufacturing & Logistics (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
To address the increasingly prominent environmental pollution and energy shortage, many countries devote themselves to green manufacturing and logistics in which some optimization problems are common and challenging, e.g., production planning and scheduling, supply chain management, location and allocation problems, vehicle routing problem, resource optimization, and pricing strategies. The present reprint contains all of the articles accepted and published in the Special Issue "Mathematical Modeling and Intelligent Optimization in Green Manufacturing & Logistics" from the MDPI Mathematics journal. This Special Issue is focused on collecting recent mathematical modeling and intelligent optimization research in green manufacturing and logistics, including operations research, game theory, (meta)heuristics, machine learning, knowledge-driven, digital twin, and so on. We hope that the scientific results presented in this reprint will serve as a valuable source of documentation and inspiration to those researching the modeling and optimization of green manufacturing and sustainable logistics.